ARCC network: A blog about blogging - Wilkins, T (Adaptation and Resilience in the Context of Change Network, 2016)
Guidance from the Adaptation and Resilience in the Context of Change network on the value of researchers writing blogs to enhance the understanding, uptake and use of their research outputs in the built environment and infrastructure sectors